2021
DOI: 10.1590/1806-9649-2021v28e43
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring multinomial processes based on a weighted chi-square control chart

Abstract: Interpreting an out-of-control signal is a crucial step in monitoring categorical processes. For the Chi-Square Control Chart (CSCC), an out-of control situation does not specify if it was a process deterioration or a process improvement. For this reason, a weighted chi-square statistical control chart WSCC is proposed with different weighting categories in order to enable an accelerated disclosure of a control situation after a shift due to a deterioration of quality and on the other hand, decelerate an out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Statistical Process Control (SPC) is a collection of tools that, when applied, identifies the variability, thus enhancing the reach of a stable process whose capacity can be improved (Ali et al, 2021). Capability is the producing concept according to specification, or generically, doing with quality (Oakland;Oakland, 2018).…”
Section: Statistical Control Processmentioning
confidence: 99%
“…Statistical Process Control (SPC) is a collection of tools that, when applied, identifies the variability, thus enhancing the reach of a stable process whose capacity can be improved (Ali et al, 2021). Capability is the producing concept according to specification, or generically, doing with quality (Oakland;Oakland, 2018).…”
Section: Statistical Control Processmentioning
confidence: 99%
“…Previous studies showed that scale above 0.7, presents good consistency between the relationships (Chan, et al, 2002). Through Pearson's chi-square test (χ2), also found in Ali, et al, (2021), it was decided to eliminate the variables contained in the governance construct and their evidence as they did not demonstrate the necessary reliability for statistical purposes, and the others were submitted to "exploratory factor analysis of main components for the evaluation of their correlations", as suggested by Schreiber (2021, p.2) and similar in previous literature (MacCallum et al, 1999& Marsh et al, 1998.…”
Section: Exploratory Factor Analysis -Main Componentsmentioning
confidence: 99%